Perbedaan Tingkat Stres Akademik Ditinjau dari Penggunaan Strategi Coping Stress pada Mahasiswa Psikologi UNP - Habibullah Maulana A; Afiful Adrian; Ilham Fitra; Maysaroh Hanifa Resti; Raudhatul Fitri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Differences in Academic Stress Levels Judging from the Use of Stress Coping Strategies among UNP Psychology Students. This research aims to see differences in academic stress levels in terms of the use of stress coping strategies. The population in this study were psychology students at Padang State University with a sample of 41 participants. The hypothesis testing analysis technique used in this research is non-parametric One Way Anova analysis. The hypothesis of this research is H1 which states that there is a difference in the level of academic stress in terms of the use of stress coping strategies, and H0 which states that there is no difference in the level of academic stress in terms of the use of stress coping strategies. This research is a quantitative comparative type using the Perceived Academic Stress Scale (PASS) Bedewy & Gabriel (2015) modified by Ni Putu Regina Pramesta Putri (2021) and the Brief COPE stress coping scale compiled by Carver (1997). The results of data analysis show that there is no significant difference in the level of academic stress in terms of the use of stress coping strategies among UNP psychology students. Apart from that, the results of data analysis also show that UNP psychology students use more stress coping with the emotional focus coping type, and the average stress level of UNP psychology students is in the medium category and none is in the low category.